L1CAM promotes enrichment of immunosuppressive T cells in human pancreatic cancer correlating with malignant progression. Issue 5 (2nd April 2014) - Grage-Griebenow, Evelin; Jerg, Elfi; Gorys, Artur; Wicklein, Daniel; Wesch, Daniela; Freitag-Wolf, Sandra; Goebel, Lisa; Vogel, Ilka; Becker, Thomas; Ebsen, Michael; Röcken, Christoph; Altevogt, Peter; et al.
Abstract : Regulatory T cell (T‐reg) enrichment in the tumor microenvironment is regarded as an important mechanism of tumor immune escape. Hence, the presence of T‐regs in highly malignant pancreatic ductal adenocarcinoma (PDAC) is correlated with short survival. Likewise, the adhesion molecule L1CAM is upregulated during PDAC progression in the pancreatic ductal epithelium also being associated with poor prognosis. To investigate whether L1CAM contributes to enrichment of T‐regs in PDAC, human CD4+CD25+CD127−CD49d− T‐regs and CD4+CD25− T‐effector cells (T‐effs) were isolated by magnetic bead separation from blood of healthy donors. Their phenotype and functional behavior were analyzed in dependence on human premalignant (H6c7) or malignant (Panc1) pancreatic ductal epithelial cells, either exhibiting or lacking L1CAM expression. T cells derived from blood and tumors of PDAC patients were analyzed by flow cytometry and findings were correlated with clinical parameters. Predominantly T‐regs but not T‐effs showed an increased migration on L1CAM expressing H6c7 and Panc1 cells. Whereas proliferation of T‐regs did not change in the presence of L1CAM, T‐effs proliferated less, exhibited a decreased CD25 expression and an increased expression of CD69. Moreover, these T‐effs exhibited a regulatory phenotype as they inhibited proliferation of autologous T cells. Accordingly, CD4+CD25−CD69+ T cells were highly abundant in PDAC tissues compared to blood being associated with nodal invasion and higher grading in PDAC patients. Overall, these data point to an important role of L1CAM in the enrichment of immunosuppressive T cells in particular of a CD4+CD25−CD69+‐phenotype in PDAC providing a novel mechanism of tumor immune escape which contributes to tumor progression. Highlights: L1CAM is expressed in chronic pancreatitis (CP) and pancreatic ductal adenocarcinoma (PDAC). L1CAM promotes the generation of immunosuppressive CD4+CD25−CD69+ T‐cells. CD4+CD25−CD69+ T cells are enriched in pancreatic tissues of CP and PDAC patients. High numbers of CD4+CD25−CD69+ T‐cells in PDAC tissues associates with malignant progression. L1CAM contributes to the generation of an immunosuppressive tumor stroma in PDAC.